Anosognosia in hoarding disorder is predicted by alterations in cognitive and inhibitory control - Peter J. van Roessel; Cassandra Marzke; Andrea D. Varias; Pavithra Mukunda; Sepehr Asgari; Catherine Sanchez; Hanyang Shen; Booil Jo; Lisa A. Gunaydin; Leanne M. Williams; Carolyn I. Rodriguez (Scientific Reports, 2022)
Abstract Insight impairment contributes significantly to morbidity in psychiatric disorders. The neurologic concept of anosognosia, reflecting deficits in metacognitive awareness of illness, is increasingly understood as relevant to psychopathology, but has been little explored in psychiatric disorders other than schizophrenia. We explored anosognosia as an aspect of insight impairment in n = 71 individuals with DSM-5 hoarding disorder. We used a standardized clutter severity measure to assess whether individuals with hoarding disorder underreport home clutter levels relative to independent examiners. We then explored whether underreporting, as a proxy for anosognosia, is predicted by clinical or neurocognitive behavioral measures. We found that individuals with hoarding disorder underreport their clutter, and that underreporting is predicted by objective severity of clutter. In an n = 53 subset of participants, we found that underreporting is predicted by altered performance on tests of cognitive control and inhibition, specifically Go/No-Go and Stroop tests. The relation of underreporting to objective clutter, the cardinal symptom of hoarding disorder, suggests that anosognosia may reflect core pathophysiology of the disorder. The neurocognitive predictors of clutter underreporting suggest that anosognosia in hoarding disorder shares a neural basis with metacognitive awareness deficits in other neuropsychiatric disorders and that executive anosognosia may be a transdiagnostic manifestation of psychopathology.